Traits of the Neolithic-Eneolithic archaeological layers’ formation at the sites of Algay and Oroshaemoe in the low Volga basin (Low Povoljie) - Vybornov, Alexandr; Yudin, Alexandr; Kulkova, Marianna; Doga, Natalija; Popov, Alexandr; Baratskov, Aleksey; Gilyazov, Filat; Somov, Anatoliy (Acta Geographica Lodziensia, 2020)
The Low Volga basin is an important area for the study on the genesis of Neolithic and Eneolithic archaeological cultures in Eastern Europe. Until now well stratified Neolithic-Eneolithic sites had not been found in the Low Volga (Low Povoljie) region. This has been a cause of serious discussion about the periodisation, genesis and interaction between cultural groups during the Late Stone Age in this area. Excavations of new open sites of Algay and Oroshaemoe began in 2014. Both sites are unique for the Low Povoljie. It is important that the archaeological layers are within loess loam and they are interlayered with sterile natural layers. This fact precludes a mixing of artefacts of different ages. Most of the artefacts and ecofacts found in a clear stratigraphic context allow for a presentation of the detailed characteristics of the Orlovskaya Neolithic culture, and the Cis-Caspian and the Khvalynskaya Eneolithic cultures. For the first time, reliable data have been obtained for a periodisation of the Neolithic-Eneolithic of the Low Povoljie. A set of radiocarbon dates for all archaeological layers allows for a determination of the precise chronological frameworks of Neolithic-Eneolithic cultures in this region. The geochemical analysis of archaeological layers and sterile interlayers made possible a reconstruction of climatic characteristics for different periods of the Holocene. The processes of development of archaeological layers in the periods of the Orlovskaya and the Cis- -Caspian cultures were considered.